Evaluación de la gestión administrativa y propuesta del plan estratégico quinquenal para el hotel libertador de la ciudad de Loja - Paredes Ortega, Víctor Antonio (2016)
The process is framed in the Hotel Liberator, a tourist company of private lodging of character, located in the city of Loja. The purpose of the investigation was to propose this procedure by means of a descriptive study with field design, and a population that was represented by 20 employees and 383 clients, who offered the information required through main diverse evaluatorias and with the help of an interview to gather the necessary data on the execution of the process. Once studied the procedures the following results were determined: 1. The induction process: It was necessary to develop 4 work meetings with all the Proprietors, Directive and the Human Talent of the Hotel with the objective of introducing them in the project and with the purpose that they know the evaluation procedures. The obtained result allowed to cooperate in the procedure and to apply the proposed study. 2. The Evaluation of the Human Acting: In consideration that the Hotel doesn't have historical information on a similar procedure it was extremely satisfactory to register that the biggest strength in this tourist company is sustained in its Human Talent. The individual, departmental and managerial results show an acting average of 516 points, equivalent to a 77.01% that throw a level of Very Good acting. 3. The following process in course was to determine the labor atmosphere as a development factor in the tourist companies; this has for objective, to know the influence of the organizational climate in the development of the activities. Their development was taken under a quantitative focus because he/she allowed to discover current conditions, he/she investigated relationships, in turn he/she studied cause phenomena and effect, the level of investigation of explanatory type was chosen, because it was interpreted and he/she thought about a possible explanation of the problem; it was based on a non-experimental design - traverse that allowed to analyze the variables of the investigation without having to intervene for its modification or change; the scenario was the interior of the referred company. The Survey of Labor Satisfaction was divided in two parts. The first considered 20 factors that should be determined in an order that he/she keeps correspondence with the grade of importance that you/they have for each collaborator according to their individual perception. The heady result established a punctuation of 144 in the value average of the factors, equivalent to 74, 23% with a grade of equivalent importance to I = Important. In the second part of the noted previously it interviews 60 questions classified in 20 factors subject to the individual perception of the participants were exposed of whose procedure a result equivalent average of factors was obtained at 6,74 that it represents an even level of satisfaction with the decoder S that represents Satisfied. 4. Another of the tools that is given to this procedure in the tourist current company is to know the level of their clients' satisfaction, the focus costumer has transformed hence into the great main character of all the companies that you/they want to remain with success in the market, it is necessary to go to technical quantitative or qualitative to measure it and to analyze it. It could be carried out this fieldwork in the moment and place that the present sample was made, for telephone, via postcard or on line. It allowed the clients that stopped to visit the Hotel to recognize or they presented some birdcall type. This information contributed knowledge on the variables of the service that are failing, to be able to act and to correct the possible areas with necessity of improvement. Among the results of the procedure they highlight with 23,00% that the option that influences in a decisive way to transform into client of the Hotel is the corporate image, what most of the clients it uses the services for more than 4 years with an equivalent value to 52,00% of those consulted. That the main place of the guests' origin is the city of Cuenca and the city of Cariamanga with an equivalent value to 58,00% and 26,00% respectively. 50,00% spends the night in the city for work causes with a weekly equivalent preponderant rhythm at the 31,00% The product and/or service with more demand are the lodging with 34,00% of the preferences, while the approach about the quality of the foods identifies the good alternative with 47,00%. The requirement has more than enough products and/or services that the Hotel doesn't offer it considers the product all included one with a 23,00 of the preferences and 37,00 equivalent% to 140 people they demand daily transport to the airport. The users of the service refer in 26,00% that the Hotel hardly ever maintains them informed on their promotions; and, they consider that the departmental units that blunt on the rest with a level of excellent, good attention, to regulate and bad they are respectively the Units of Rooms, Reception and Accounting in the last two cases, however that in general they assure to have had a good attention with an equivalent value at the 23,00% Guests that use other additional services that he/she offers the Hotel, hardly exist because only the 23,00% refers to have used them in several opportunities. The guests in an equivalent percentage to 48,00% consider that the prerequisites to consent to a room reservation are easy and that the received attention was opportune. However only the 4,00% believes that the quality of the services in comparison with that of other hotels is excellent. The perception of the prices with relationship to other hotels in 31,00% refers that they are exaggerated and they manifest in 25,00% that the stimuli that you/they want to receive are discounts in the price of the lodging, however that the products and services that he/she offers the Hotel in comparison with other local hotels are satisfactory in a measure of the 18,00% The18,00% of those interviewed wants to be informed of the products and services that would offer the Hotel through television. The Hotels that you/they choose when one cannot assist their lodging requirements and feeding they are Great Victoria Boutique Hotel, Howard Johnson and the Hotel Ramsés with 27,00%, 26,00% and 19,00% respectively. It is important to point out that 11,00% of the clients doesn't want to continue being client of the Hotel Liberator. 5. The Strategic Plan contains among its elements a Presentation like antecedent to the Methodology contained in a Situational Diagnosis and in the Characterization of the tourist Industry at local and regional level. The Strategic Plan defines the Direct Competitors in base of the information Not obtained in the question. 24 of the Survey of Satisfaction of the Client. It is designed the Vision and the Mission of the competitive strategy, as well as the Politicians of Quality and the Corporate Values. Among the Managerial General and Specific Politicians that will govern to the Hotel during the development of the Five-year Plan the opportunities of growth that he/she has the company are born and 5 wombs are generated, each one with an objective and an itemized analysis FODA to more than Potentialities, Challenges, Risks and Limitations, analyzed from the strategic competitive perspective. The Proposal of Value is included, the competitive position of the offered products, the Strategic Map and the Strategic Objectives in a perspective womb generating individual responsibilities and in group for its development. 6. P.O.A. it considers the following elements: A leaf summary of the economic financial activity of the Plan through: I foment Tourist, I Spend Current, Expense Remunerations, Eventual Expense, Fund of Self-management and the Projection of Revenues for the period. 7. Finally the Plan of Marketing includes the strategic elements for the execution of the process of induction of the sale of the products and offered services.